2017
DOI: 10.1007/s11999-015-4644-8
|View full text |Cite|
|
Sign up to set email alerts
|

What Are the Long-term Results of MUTARS® Modular Endoprostheses for Reconstruction of Tumor Resection of the Distal Femur and Proximal Tibia?

Abstract: BackgroundModular endoprostheses are commonly used to reconstruct defects of the distal femur and proximal tibia after bone tumor resection. Because limb salvage surgery for bone sarcomas is relatively new, becoming more frequently used since the 1980s, studies focusing on the long-term results of such prostheses in treatment of primary tumors are scarce.Questions/purposes(1) What proportion of patients experience a mechanical complication with the MUTARS® modular endoprosthesis when used for tumor reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 36 publications
2
78
1
4
Order By: Relevance
“…The data provided by Bus et al [3] indicates that the MUTARS 1 system appears comparable to other systems in terms of implant survival. Owing to heterogeneity among tumor patients in terms of tumor biology, demographic parameters or extent of the defect, there is a need for large series with standardized description of the these parameters.…”
Section: Where Do We Need To Go?mentioning
confidence: 87%
See 1 more Smart Citation
“…The data provided by Bus et al [3] indicates that the MUTARS 1 system appears comparable to other systems in terms of implant survival. Owing to heterogeneity among tumor patients in terms of tumor biology, demographic parameters or extent of the defect, there is a need for large series with standardized description of the these parameters.…”
Section: Where Do We Need To Go?mentioning
confidence: 87%
“…The study by Bus et al [3] focuses on both the complication and long-term performance of the modular MUTARS 1 prosthetic implant design. The study also describes the applicability and reliability of this implant design.…”
mentioning
confidence: 99%
“…Structural failures were observed in 7% of the cases including prosthesis breakage, periprosthetic fractures, and articular hinge or polyethylene liner failures. Bus et al reported a 14% structural failure rate of MUTARS® knee prostheses after a mean of three years, consisting of fractures and unlocking of the locking mechanism, instances of wear, fractures of the femoral component, and stem fractures [6]. Ilyas et al reported about one femoral stem fracture of a HMRS prosthesis three years after surgery [9].…”
Section: Discussionmentioning
confidence: 99%
“…Patients should be alerted to this possibility so that if they do have any bacterial infection they can receive suitable treatment in a timely manner, thus avoiding contamination of the allograft. With learning such measures through experience, we have been able to reduce the number of complications. Another consideration regarding infection is sterility of the allograft.…”
Section: Discussionmentioning
confidence: 99%